Wilson meets members of the opposition party the United Peoples Party. From left to right: Wilson, Gondo (glasses), Chipunza, Mkudi
Wilson meets members of the opposition party the United Peoples Party. From left to right: Wilson, Gondo (glasses), Chipunza, Mkudi.